Application of FMEA and Methodologies in Service Delivery GUT Automotive Laser Geometry - Cembranel, Priscila; Lopes, Luis Felipe Dias (Revista de Administração da UFSM, 2015)
The automotive service geometry laser is responsible for wheel alignment, steering and camber and aims to adjust the wheels so the tire has the least possible friction with the ground. We selected the service Geometry laser due to its high demand in the company under study (verified by the sales reports and service orders), with respect to sales volume. The study aimed at the development of process flowchart, identifying failures in suggesting and implementing actions to correct the non-conformities. The methodology we used the quantitative approach, methodology and descriptive as technical monitoring in situ, in order to identify all steps involved in the process of providing the service. For the identification of faults used the FMEA method was evaluated using criteria from methodology GUT. The main faults listed were: the high rate of rework, the qualification of contractor geometry, the need to update the manual of standards and measures for the vehicle geometry, the need for monitoring contractor geometry with the client in the vehicle testing and calibration and verification machine geometry. Through the methodology GUT has listed as priority monitoring the contractor geometry with the client in the vehicle testing and measuring equipment geometry, which directly impacted the index rework.